2017
DOI: 10.3390/ijms18071519
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin and Its Angiogenic Activity

Abstract: Erythropoietin (EPO) is the main hematopoietic hormone acting on progenitor red blood cells via stimulation of cell growth, differentiation, and anti-apoptosis. However, its receptor (EPOR) is also expressed in various non-hematopoietic tissues, including endothelium. EPO is a pleiotropic growth factor that exhibits growth stimulation and cell/tissue protection on numerous cells and tissues. In this article we review the angiogenesis potential of EPO on endothelial cells in heart, brain, and leg ischemia, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 99 publications
2
62
0
3
Order By: Relevance
“…We conclude that the virulence of SARS-CoV-2 is reduced at high-altitude due to the physiological acclimatization of its inhabitants, and due to particular environmental characteristics. Furthermore, additional physiological acclimatization of high-altitude living associated with increased ventilation (Soliz et al 2005), augmented arterial oxygen transport (Lundby et al 2007), and higher tissue oxygenation (Kimakova et al 2017), mainly (but not exclusively) mediated by erythropoietin could be explored for potential therapy (see Soliz et al, 2020, same issue RSPNB) of acute respiratory distress associated with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that the virulence of SARS-CoV-2 is reduced at high-altitude due to the physiological acclimatization of its inhabitants, and due to particular environmental characteristics. Furthermore, additional physiological acclimatization of high-altitude living associated with increased ventilation (Soliz et al 2005), augmented arterial oxygen transport (Lundby et al 2007), and higher tissue oxygenation (Kimakova et al 2017), mainly (but not exclusively) mediated by erythropoietin could be explored for potential therapy (see Soliz et al, 2020, same issue RSPNB) of acute respiratory distress associated with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid establishment of a sufficient vascularisation is crucial for the in vivo survival and long-term function of tissue-engineered constructs (Laschke et al, 2006;Novosel et al, 2011). Since the ingrowth of blood vessels from the surrounding host tissue into the implants is a time-consuming angiogenic process, sophisticated pre-vascularisation strategies have recently been developed (Muscari et al, 2014;Laschke and Menger, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Of interest for skeletal tissue engineering, the pleiotropic capabilities of EPO include osteogenic and angiogenic potencies. (6)(7)(8)(9)(10) The studies coupling the EPO to bone healing reported that the use of EPO was supraphysiologic dosage and had potential harmful implication like high blood viscosity and consecutive thromboembolic events. Many researches shifted to the use of topical administration of EPO into the bone defect to improve the efficiency of EPO on the bone formation with minimal systemic effect.…”
Section: Discussionmentioning
confidence: 99%